Refresh organic electrodes for high-power and long-cycle applications - Wenlu Sun; Yulu He; Lei Fang; Jinrong Zeng; Enli Tang; Tingping Hu; Hui Zhang; Derong Lu; Chenji Hu; Zhilong Quan; Huabin Kong; Hongwei Chen (Nature Communications)
Abstract Enhancing the durability of electrodes under high-power conditions is crucial for advancing high-power secondary batteries. Despite numerous optimization strategies proposed to mitigate electrode structural degradation, the performance of common electrodes inevitably deteriorates under high currents over extended cycling life. In this study, we report a capacity refreshing strategy for a porous organic framework electrode operating under high power conditions. By intermittently applying low currents, deactivated ions trapped within the framework can be effectively released, thus refreshing the electrode’s capacity. Importantly, this capacity refreshing can be periodically repeated. The framework electrode thus achieves an extended cycle life of over 60,000 cycles at 20 C (6 A/g) with a specific power of 28 kW/kg (based on active material). This strategy represents an alternative concept for designing organic electrodes that combine high power and long cycle life.